THE ANALYSIS OF BEHAVIORAL RISK FACTOR OF DIARRHEA OUTBREAK IN TIRTOMARTO VILLAGE, CENTRAL JAVA - Eny Dwimawati; Ade Saputra Nasution; Evalina Franciska Hutasoit (Jurnal Berkala Epidemiologi, 2022)
Background: Outbreak Diarrhea in Indonesia still threatens the health and even fatal results, namely death. It is caused by unsanitary and healthy behaviors Purpose: This research aims to find out behavioral risk factors that influence the occurrence of diarrhea outbreaks. Methods: This study used a cross-sectional design with a sampling of 65 people was taken from the population of 180 diarrhea cases using a simple random sample in Tirtomarto, Central Java. The chi-square test was then applied to analyse the data. Measured variables are risky behavior (washing hands with soap before eating, washing hands with soap after defecating, the habit of closing food, soap usage for washing utensils and the place of defecation). Results: It is found that the risk factors for unusual diarrhea behavior are washing hands with soap before eating (p = 0.01), washing hands with soap after defecation (p = 0.01), the habit of washing utensils with soap (p = 0.73), the habit of covering food (p = 0.01), bowel habits (p = 0.73). Multivariable analysis results found that the most dominant behavioral risk factors are handwashing with soap after defecation (OR = 0.11) and the habit of covering food (OR = 0.12). Conclusion: Behavioral risk factors can influence the occurrence of outbreaks of diarrhea.